Debaryomyces hansenii UFV-1 intracellular α-Galactosidase characterization and comparative studies with the extracellular enzyme - Rezende, Sebastião T. de; Viana, Pollyanna A.; Passos, Flávia Maria Lopes; Oliveira, Jamil S.; Teixeira, Kádima N.; Santos, Alexandre M. C.; Bemquerer, Marcelo P.; Rosa, José C.; Santoro, Marcelo M.; Guimarães, Valéria M. (Journal of Agricultural and Food Chemistry, 2009)
Debaryomyces hansenii cells cultivated on galactose produced extracellular and intracellular α-galactosidases, which showed 54.5 and 54.8 kDa molecular mass (MALDI-TOF), 60 and 61 kDa (SDS−PAGE) and 5.15 and 4.15 pI values, respectively. The extracellular and intracellular deglycosylated forms presented 36 and 40 kDa molecular mass, with 40 and 34% carbohydrate content, respectively. The N-terminal sequences of the α-galactosidases were identical. Intracellular α-galactosidase showed smaller thermostability when compared to the extracellular enzyme. D. hansenii UFV-1 extracellular α-galactosidase presented higher kcat than the intracellular enzyme (7.16 vs 3.29 s^−1, respectively) for the p-nitrophenyl-α-d-galactopyranoside substrate. The Km for hydrolysis of pNPαGal, melibiose, stachyose, and raffinose were 0.32, 2.12, 10.8, and 32.8 mM, respectively. The intracellular enzyme was acompetitively inhibited by galactose (Ki = 0.70 mM), and it was inactivated by Cu(II) and Ag(I). Enzyme incubation with soy milk for 6 h at 55 °C reduced stachyose and raffinose amounts by 100 and 73%, respectively.
Keywords: Characterization; Debaryomyces hansenii UFV-1; Deglycosylation; Galacto-oligosaccharides; α-Galactosidases